Teaching English Writing at the Secondary Level in Vietnam: Policy Intentions and Classroom Practice - Chi, Nguyen Thi Kim (VNU Journal of Science: Education Research, 2022)
The need for writing is undoubtedly pervasive in our lives, especially in modern societies of the 21 st century. When examining the everyday world, one finds people engaged in many varieties of writing such as sending a text message, writing a covering letter or a scholarship application form, composing a research paper, etc. In short, writing not only is an integral part of our social and professional activities but also determines our life chances. The growth of English as a lingua franca makes English writing more important than ever before, which results in more attention paid to teaching English writing in non-English speaking contexts. This paper reports on part of the findings of a study that investigated practices of teaching English writing at the lower secondary level in Ba Ria-Vung Tau, Vietnam. The research employed a qualitative, multi-case study approach. The findings revealed a significant gap between the English education policies of the Vietnamese government and classroom practice. The teaching of secondary English writing did not prepare learners well for the 21 st century language skills as expected.